Wakra Meke terhadap Kearifan Lokal dan Ketahanan Pangan Masyarakat Desa Imroing Kecamatan Pulau-Pulau Babar Kabupaten Maluku Barat Daya - Yehuda Unwaru; August E Pattiselanno; Stephen F. W. Thenu (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2022)
In order to understand the value of local wisdom in wakra meke and to assess the function of wakra meke for the people of Imroing Village's access to food, this study attempts to determine the process of local wisdom in wakra meke. Participant observation techniques, in-depth interviews, and documentation were used to conduct this study. A qualitative descriptive analysis that took the form of written words was used to analyze the data. The study's findings demonstrate that wakra meke is a local wisdom of the Imroing Village community that has persisted since the days of the ancestors and is still used by the farming community to ensure the year-round availability of food supplies. Wakra meke is made both corn on the cob and corn on the cob that has been sun-dried to dry. Wakra meke is a staple meal that contributes to community food security. It is also utilized as a means of income by being sold to customers. Wakra meke is one of the local wisdoms.